Fakery and Wealth in African Charismatic Christianity: Moving beyond the Prosperity Gospel as Script - Lauterbach, Karen (Faith in African Lived Christianity, 2020)
The prosperity gospel – the promise of abundant wealth as a sign of God’s blessing – is one of the most prominent features of charismatic Christianity in Africa, and also one of the most contested. In many of the popular charismatic mega-churches in Ghana, Kenya, Nigeria, and Uganda, pastors preach the health and wealth gospel; they promise material wealth to congregants as a sign of God’s blessing and at the same time strongly encourage church members to give generously in church. Many prosperity pastors are themselves illustrations of what they preach, living in big houses and driving luxury cars; some
free